Clay work and body image in art therapy : using metaphor and symbolism to heal - Crocker, Trisha; Carr, Susan M. D. (New York : Routledge, 2021)
"Clay Work and Body Image in Art Therapy provides an important addition to resources available in the field of clay work and art therapy, highlighting the unique sensory aspects of the medium and its ability to provide a therapeutic resource for women who experience body image issues. Chapters offer a comprehensive distillation of current knowledge in the field of body image, clay work, neuroscience, and art therapy, building a theoretical framework around personal narratives. Case studies examine the benefits of exploring body image through clay work within art therapy practice, providing a positive and contained way to find personal acceptance and featuring photographs of clay body image sculptures created by research participants that highlight their individual stories and experiences. As well as offering both clinical and practical implications, the text provides a full protocol for the research and evaluation methods carried out, enabling further replication of the intervention and research methods by other therapists. This book highlights clay work as a significant resource for art therapists, arts in health practitioners, and counsellors, providing an emotive yet contained approach to the development of personal body image acceptance and self-compassion"--
OCLC-licensed vendor bibliographic record.
Keywords: Body image; Imagery (Psychology); Self-perception.; Art therapy; ART / Techniques / Sculpting